(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Insurance sector is a developing segment in India. Section of private and outside insurance companies has made profoundly aggressive and unpredictable condition in the insurance advertise. In such a domain, a straightforward arrangement of financial announcing is important to ensure the interests of policyholders and different partners. Present study, Corporate Reporting Practices of Insurance Sector in India is led to break down the financial announcing practices of life and general insurance companies. The investigation depends on the yearly reports of Indian insurance companies for a time of 8 years for example from 2002-03 to 2009-10. Different records for example compulsory exposure file, intentional divulgence file and record identifying with corporate governance things are built. Unweighted exposure scores are utilized to dissect the financial detailing practices of these companies.